Lepromatous leprosy. Case presentation - Carlos Alberto Blanco Córdova; Mailin Claxton Louit (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Leprosy is an infectious and contagious disease, of chronic evolution produced by Micobacterium Leprae which affects skin and nerves In its most severe form it also affects internal organs. As old as men, patients who suffer from it continue marginalized and stigmatized as it occurred thousand of years ago. World Heath Organization (WHO) has developed a program oriented  to diagnose it timely and treat it adequately. Many times patients with leprosy are diagnosed in the second health care level, accompanied by irreversible disabilities due to late diagnosis. For this reason we think it is necessary to present a case of Lepromatous Leprosy, diagnosed in the health area (primary health care) and in an early stage of the disease , which interrupts the epidemiological chain and avoids the frightening associated disabilities which end in social inability, with all the psychological effects for the patient and his family. It is of great importance to continue preparing the Health Basic Team (BHT) an d the Work Basic Group (WBG) to make early diagnosis of leprosy in the primary health care , as the one presented in this work to fulfill the duty of eradicating this disease in the country.